AUCH GEHÖRLOSE LERNER KÖNNEN FREMDSPRACHEN LERNEN - Skowronek, Barbara (Scripta Neophilologica Posnaniensia, 2019)
How do the deaf people learn to communicate? Can the deaf people learn the phonic language (sound language, germ. lautsprachlich kommunizieren); can they learn foreign languages? What conditions should be met for this? What support should they expect from the family, from teachers, from hearing people? The answer to this will be a description of Sarah Neef’s learning the sound language.